Analysing The Understanding Of Childfree Practitioners From Islamic Academia On The Hadith About Multiplying Offspring - Fitria, Riri (Jurnal Ushuluddin, 2024)
Childfree has been a phenomenon that has attracted public attention since its emergence in 2013. There is opposition in society to childfree because it goes against human instinct and nature and Indonesian culture that understands many children's sustenance. This article investigates the childfree trend among Islamic academics, exploring their understanding of the hadith that explicitly encourages Muslims to multiply offspring by taking into account the social dynamics that influence this understanding and choice. The research uses a qualitative method with a descriptive approach, through in-depth interviews with seven Islamic academics who choose to go child-free. The results show that in understanding the hadith they tend to understand it contextually. This leads to the conclusion that the hadith is a recommendation, not an obligation, for married couples who have mental readiness, physical health, economic stability, and desire to have children. Other things that influence this understanding are spousal support and the great challenges of educating children today. Despite facing social pressures, the informants maintained their commitment to being child-free but remained open to re-evaluating in the future. This study highlights the complexity of childfree decision-making, which is influenced by personal, social and religious factors